Uji aktivitas antiinflamasi kombinasi ekstrak etanol rimpang kencur (kaempferiae galangal l.) dan daun tapak dara (catharanthus roseus) pada tikus - Galih Samodra1; Ikhwan Yuda Kusuma (Universitas Borneo Lestari, 2021)
This study aims to determine the anti-inflammatory activity by using a combination of extracts, namely kencur rhizome (Kaempferiae galanga L.) and tapak dara leaf (Catharanthus roseus). This research method was carried out experimentally, the data were analyzed using the One Way ANOVA (Analysis of Variant) method with sig = 0.05 to determine the significant difference between the control group, test group. If F count > F table means that there is a significant difference, then it is continued with a further test, namely the Tukey HSD test. All data were calculated using the Windows SPSS program. The results of this study showed that the percentage of inhibition of the combination of kencur rhizome extract and tapak dara leaf was greater than that of the single administration. It can be seen that the highest percentage of inhibition of the extract combination was found at the 60th and 120th minutes with values ​​of 63.63% and 63.63%, respectively followed by kencur rhizome at the same minute with values ​​of 59.09% and 59.09% and finally tapak dara leaves at 58.44% and 58.44%, respectively. Based on the results of the SPSS test with the Tukey test, there was no significant difference between the positive control group and all treatment groups, which means that the use of a combination or single extract has anti-inflammatory activity from both extracts. Significantly different results were seen when compared to the negative control which was only given Na-CMC